Gender Differences in Smartphone App Use by Undergraduate Students - Salas, Jessi; Rubio, Karen R.; Stokes, Bryonna; Spann, Tyime; Winslow, Niyla H.; Wright, Anthony T. (My University, 2020)
Smartphones are ubiquitous in modern society. The present study examined gender differences in how men and women used their smartphones. Participants were 153 men and women undergraduate students at VSU. Men used their phones to access movies and news more often than women, as well as using dating sites and gambling (p <.01). No gender differences were observed in downloading apps, downloading class notes, listening to music or making payments online. While men and women appear to use the same types of activities on their cell phones, men’s frequency of use was higher across many domains of entertainment, news and dating. Men and women were similar in frequency of smartphone app use in more common and chore-like activities.